Outcome of permanent vascular access for haemodialysis in patients with end-stage renal disease in Cameroon: results from the pilot experience of the Douala general hospital. Issue 1 (2nd January 2016) - Ngatchou, William; Ngbwa Evina, Achille; Halle, Marie Patrice; Massom, Annie; Ekane, Samuel; Basile, Essola; Origer, Pierre; Haquebard, Jean Pierre; Olinga Olinga, Alain; Jansens, Jean Luc; Watel, Alain; Lecain, Antoine; et al.
Abstract: Background Chronic Kidney disease is a major health problem in the world. Native arteriovenous Fistula (AVF) is well established as the best vascular access for haemodialysis. Little is known about the outcome of AVF in sub-Saharan Africa. We aim to analyze the outcome of patients undergoing AVF creation during the pilot program established at the Douala general hospital (DGH). Method This was hospital-based, longitudinal study with a retrospective phase (April 2010–January 2014) and a prospective phase (January 2014–April 2014). All consecutive patients operated for AVF creation were included in this study. Socio-demographics data, functionality, and complications were analyzed. Results Eighty-one patients including 52 men were enrolled in this study (49 prospectively and 32 retrospectively). The mean age was 52, 3 years (range 18–81 years). Hypertension (66, 7%), diabetes (17, 3%), and HIV (8, 6%) were the most observed co-morbidities. About 96.3% of AVF were native and 3.7% were prosthetic graft. Radiocephalic AVF was performed at a rate of 77.8%. The primary function rate was 97.7% and the mean follow-up period 43.4 weeks. The overall rate of complications was 44.4% of whom 30.5% were early, 30.5% secondary, and 39% lasted. The treatment of these complications was conservative in 48.7% of cases. Conclusions The results of the pilot program of AVF creation at the DGH are encouraging. However, the sustainability of this project requires human capacity building.